EVALUATION OF THE IMPLEMENTATION OF THE TAHFIZH SPT PROGRAM AT SMPN ACEH BESAR REGENCY: A REVIEW FROM THE PERSPECTIVE OF PLANNING AND IMPLEMENTATION - Ramadhani, Shaufi; Marzuki, Marzuki (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
This study aims to evaluate educators' and students' planning in the Integrated Education System (SPT) program in the field of tahfizh at the junior high school (SMP) level in Aceh Besar Regency. The evaluation used a quantitative approach involving 12 educators and 361 students. Data collection was carried out using a questionnaire that had undergone content validation (Aiken's) and reliability (Cronbach's Alpha). The educators' evaluation results at the planning stage averaged 4.44, with a